Synthesis and Biocompatibility of Silicone Hydrogel Functionalized with Polysaccharide - Jeong, Keun-Seung; Kim, Ho-Joong; Lim, Hwa-Lim; Ryu, Geun-Chang; Seo, Eun-Sun; You, Nam-Ho; Jun, Jin (WILEY-V C H VERLAG GMBH, 2015)
A novel methacrylated polydimethylsiloxane (mPDMS) was synthesized for the preparation of silicone hydrogel (SiHy). The SiHy was functionalized with polysaccharides such as hyaluronic acid and alginic acid by construction of an interpenetrating polymer network (IPN) structure composed of cross-linked SiHy backbones and polysaccharide networks. We investigated the protein adsorption resistance, toxicity, wettability, optical transparency, and surface property of the SiHy. The synthesized SiHy exhibited the transmittance of over 90% and the improved surface hydrophilicity. Importantly, the amount of protein adsorbed on the polysaccharide-functionalized SiHy decreased significantly compared with unmodified SiHy. These results suggest that polysaccharide-modified SiHy may offer potential for ophthalmic materials as well as antibiofouling coating materials.
Keywords: PROTEIN ADSORPTION; POLY(ETHYLENE GLYCOL); PHOSPHOLIPID POLYMER; RESISTANCE